Energy literacy and agency of New Zealand children. Issue 6 (3rd July 2017) - Aguirre-Bielschowsky, I.; Lawson, R.; Stephenson, J.; Todd, S.
Abstract : The development of energy literacy (knowledge, attitudes, and intended behaviour) and agency of New Zealand children (age 9–10) were investigated through thematic and exploratory statistical analyses of interviews (October 2011–April 2012) with 26 children, their parents and teachers, focus groups and photo elicitation. The children knew that electricity costs money and saw it as a finite resource. Half could name an energy source but few knew of any associated environmental issues. Most of the children had a positive attitude towards saving electricity, but did not intend to save energy to a further extent (low intended behaviour) and were not influencing their families to conserve energy (low agency). The children were learning about energy informally from a variety of sources, and acquired their attitudes mostly from talking to their parents. The results highlight the need for energy education for citizenship at school and conversations about energy both there and at home.